The genus Casinaria Holmgren, 1859 (Hymenoptera: Ichneumonidae, Campopleginae) from China - Han, Yuan-Yuan; Achterberg, Kees Van; Chen, Xue-Xin (Zootaxa, 2021)
The genus Casinaria Holmgren, 1859 (Hymenoptera, Ichneumonidae, Campopleginae) from China is revised. Nine new species are proposed (C. albifunda sp. nov., C. artivultis sp. nov., C. exilis sp. nov., C. exiloides sp. nov., C. hei sp. nov., C. melasoma sp. nov., C. partolstoyi sp. nov., C. remota sp. nov., and C. xui sp. nov.) and two species are recorded as new to China (C. ajanta Maheshwary & Gupta and C. varuni Maheshwary & Gupta). A key to the Chinese species of Casinaria is provided.